DAMPAK THINK PAIR SQUARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Rahmi Badri (Departemen Matematika, 2018)
Mathematical communication ability is important aspect of learning mathematics. However, in fact students’ mathematical communication ability in grade VII MTs Negeri 6 Padang was still low. Observation showed that students’ were less interest in mathematics learning which was difficult and boring. One efforts that can be done was applying cooperative learning model Think Pair Square type. Type of research was quasi experimental research with static group design. Sampling was done by simple random sampling technique. Instrument was final test. Data analysis used t test. Based on data analysis, it can be concluded that students’ mathematical communication ability who learning by cooperative learning model think pair square type is better than direct instruction.Keywords— cooperative learning model think pair square type, direct instruction, mathematical communication ability